"Real-Time" Milestone and Surgical Skills Feedback: A Multi-center Trial of "myTIPreport". (October 2016) - Connolly, AnnaMarie; Blanchard, Anita; Gerber, Susan; Amundsen, Cindy; Dunivan, Gena; Litwiller, Abigail
Abstract : BACKGROUND: Feedback is valued and effective when provided in a timely fashion. This can prove challenging in busy clinical settings. METHODS: OBGYN residency and FPMRS fellowship programs participated from November 2014 to May 2015. OBGYN residents and teachers and FPMRS fellows and teachers completed a pre-survey on satisfaction with venue-based feedback. Questions addressed satisfaction with feedback frequency, quality, and timeliness. After 6 months of myTIPreport use for feedback on ACGME-required milestones and select surgical procedures, participants completed a post-survey. RESULTS: Participants represented 12 OBGYN residency and 7 FPMRS fellowship programs. Pre-surveys were completed by 273 learners (254 OBGYN residents/19 FPMRS fellows) and 383 teachers (355 OBGYN/28 FPMRS teachers). OBGYN residents reported low rates of satisfaction with feedback received regarding frequency (38%), quality (42%) and timeliness (37%). OBGYN and FPMRS teachers reported low rates of satisfaction with feedback given (50%/54%/54%, and 39%/54%/39%, respectively). Post-surveys were completed by 207 participants. For the primary study outcome, OBGYN residents (n=77), OBGYN teachers (n=96), and FPMRS teachers (n=19) reported significantly improved satisfaction with feedback frequency, quality, and timeliness from rates of 37–54% to rates of 60–100% ( P <.0001 for all domains). Feedback satisfaction remained high for FPMRS fellows (n=15). DISCUSSION: myTIPreport was successfully implemented at multiple institutions within 6 months. Resident and teacher satisfaction with feedback improved significantly after using myTIPreport.